Applications of Fixed Point Theory to Investigate a System of Fractional Order Differential Equations. (29th September 2021) - Khan, Zareen A.; Ahmad, Israr; Shah, Kamal
Abstract : We investigate a nonlinear system of pantograph-type fractional differential equations (FDEs) via Caputo-Hadamard derivative (CHD). We establish the conditions for existence theory and Ulam-Hyers-type stability for the underlying boundary value system (BVS) of FDE. We use Krasnoselskii's and Banach's fixed point theorems to obtain the desired results for the existence of solution. Stability is an important aspect from a numerical point of view we investigate here. To justify the main work, relevant examples are provided.